Pengaruh Pemberian Kompensasi, Motivasi dan Semangat Kerja terhadap Kinerja Pegawai Dinas Pendidikan Provinsi Aceh - Muhammaddar; Win, Konadi (Aceh Cooperative Care, 2023)
The aim of the study was to analyze the effect of compensation, motivation and morale on the performance of the Aceh Province Education Office employees. Collecting data through questionnaires to 121 employees who were tested for validity and reliability. Associative research method with data analysis through parametric statistics with path analysis. Based on the results of the study it was concluded that there is a causal relationship between variables: (1). compensation and motivation in the moderate category (0.609), (2) motivation and morale in the moderate category (0.617). (3) moral and compensation variables are in the moderate category (0.569). The results of the data analysis prove that there is a direct and indirect effect of compensation on employee performance of 59.54%, motivational variables on employee performance of 53.02%, and moral aspects of employee performance of 50.09%. Simultaneously, the three factors, namely compensation, motivation and morale, made a positive contribution to improving the performance of employees of the Aceh Province Education Office, namely 62.5%.